Answer:
A.
Explanation:
![y=2x+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bhepqiq76mgdvb7p1s7alf3odob1dpvlak.png)
![y=x^2+x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/29vsxed6v866xehnn2dsprhzs2dcm9f1o3.png)
Both equations are solved for y so I'm just going to substitute
the 1st y (the 2x+4) into the second equation's y.
![2x+4=x^2+x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r7xs9gyn26tjkayxm1pr7qb07kk0z8e1rw.png)
I'm going to get everything on one side so I have 0=ax^2+bx+c.
Subtract 2x and subtract 4 on both sides:
![0=x^2-x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/57l22pb8hvc34ctdbd3ub01mly9y46mt68.png)
Since the coefficient of x^2 is 1, all we have to do is find two numbers that multiply to be -6 and add up to be -1.
These numbers are -3 and 2.
So the factored form of our equation is:
![0=(x-3)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/txdb9ga4nzikmuir0qezrlbaghcdaez2ah.png)
This means we have x-3=0 or x+2=0.
x-3=0
Add 3 on both sides:
x=3
x+2=0
Subtract 2 on both sides:
x=-2
So now we need to find y. I'm going to choose to use the easier equation:
y=2x+4.
If x=3, then y=2(3)+4=6+4=10. The ordered pair (3,10) is a solution.
If x=-2, then y=2(-2)+4=-4+4=0. The orded pair (-2,0) is a solution.